2012
DOI: 10.2174/187152812800392832
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics as an Alternative Strategy for Prevention and Treatment of Human Diseases: A Review

Abstract: Probiotics are live microbial food supplements or their components, which have been shown to have beneficial effects on human health. Probiotics can be bacteria, molds, or yeasts, but most of them fall into the group known as lactic acid bacteria and are normally consumed in the form of yogurt, fermented milk, or other fermented foods. Data from clinical trials have shown contrasting effects and should be interpreted with caution. A large variety of potential beneficial effects have been reported including imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 0 publications
0
46
0
6
Order By: Relevance
“…Clinical studies have found that [40]. In addition, many studies reported that probiotics, and homogenates of lactic acid bacteria are effective for preventing cancer [29], improving absorption of lactose and milk proteins [15], decreasing cholesterol [42], treating rheumatoid arthritis [5], and enhancing intestinal regulation [20]. Thus, in terms of the functionality of lactic acid bacteria, this study confirmed that antimicrobial and anti-allergic activity was increased by culturing the lactic acid bacteria in a medium containing the supernatant of lactic acid bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical studies have found that [40]. In addition, many studies reported that probiotics, and homogenates of lactic acid bacteria are effective for preventing cancer [29], improving absorption of lactose and milk proteins [15], decreasing cholesterol [42], treating rheumatoid arthritis [5], and enhancing intestinal regulation [20]. Thus, in terms of the functionality of lactic acid bacteria, this study confirmed that antimicrobial and anti-allergic activity was increased by culturing the lactic acid bacteria in a medium containing the supernatant of lactic acid bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The microplate was then washed, 100 μl of substrate solution was added to each of the wells, and the wells were then incubated at room temperature in a dark room for 30 min. 50 μl of a stop solution was added to each of the wells, and the wells were measured at an absorbance of 450 nm using a microplate spectrophotometer (ELISA reader, Molecular Devices, CA, USA) [20,32].…”
Section: Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common microorganisms in probiotic preparations that possess health benefits are lactic acid bacteria (LAB), mainly lactobacilli and bifidobacteria. Probiotics have been reported to improve intestinal tract health, enhance the immune system, reduce symptoms of lactose intolerance, decrease the prevalence of allergy, treat colitis and lower serum cholesterol levels [61][62][63].…”
Section: Characteristics and Health Benefits Of Probioticsmentioning
confidence: 99%
“…The administration of probiotics has demonstrated that they can notably reduce cholesterol levels [31,32].…”
Section: Reduction Of Cholesterol In the Presence Of Bile Saltsmentioning
confidence: 99%